A Study On Wayfinding System In National Museum Kuala Lumpur - Othman, Muhammad Fikri Saidi; Mohd Narawai, Nur Fatin Athirah; Zakaria, Muhammad Salehuddin (Idealogy Journal, 2022)
Wayfinding is an important element that has long existed since  the 15th century again to help people to go to places of interest through visuals that are icons, symbols, signboards, and navigation. However, today there are still areas of public attractions that have wide space as museums still do not take full advantage of the benefits of the wayfinding system to the community. This has been proven through pilot studies conducted in several large-capacity museums such as the National Museum, Sultan Alam Shah Museum and Perak Museum. Based on the questions given to the visitors, more than 80% said they faced the confusion to understand historical storytelling while in the museum. This study will provide improvements to the existing wayfinding system at the selected museum, the National Museum to give visitors the benefits and attractions of the museum. Keywords: Wayfinding system; national museum; public attraction.